Patient safety culture at neonatal intensive care units: perspectives of the nursing and medical team - Andréia Tomazoni; Patrícia Kuerten Rocha; Sabrina de Souza; Jane Cristina Anders; Hamilton Filipe Correia de Malfussi (Universidade de São Paulo, 2014)
OBJECTIVE: to verify the assessment of the patient safety culture according to the function and length of experience of the nursing and medical teams at Neonatal Intensive Care Units.METHOD: quantitative survey undertaken at four Neonatal Intensive Care Units in Florianópolis, Brazil. The sample totaled 141 subjects. The data were collected between February and April 2013 through the application of the Hospital Survey on Patient Safety Culture. For analysis, the Kruskal-Wallis and Chi-Square tests and Cronbach's Alpha coefficient were used. Approval for the research project was obtained from the Ethics Committee, CAAE: 05274612.7.0000.0121.RESULTS: differences in the number of positive answers to the Hospital Survey on Patient Safety Culture, the safety grade and the number of reported events were found according to the professional characteristics. A significant association was found between a shorter Length of work at the hospital and Length of work at the unit and a larger number of positive answers; longer length of experience in the profession represented higher grades and less reported events. The physicians and nursing technicians assessed the patient safety culture more positively. Cronbach's alpha demonstrated the reliability of the instrument.CONCLUSION: the differences found reveal a possible relation between the assessment of the safety culture and the subjects' professional characteristics at the Neonatal Intensive Care Units.